The Optimization of the Fillet Size of Autoclave Tooth Based on the Experiment and Numerical Simulation - Xiaoping Ouyang; Zhijian Ye; Pengcheng Lin; Yanping Li (Advances in Materials Science and Engineering)
Focusing on the phenomenon of the crack on the autoclave flange, a three-dimensional model of the autoclave was established based on the Ansys Workbench platform. A new finite element analysis flow for optimizing the design of autoclave teeth was established using the Fluent, Static Structure, and Direct Optimization modules. The paper analyzed and discussed the maximum stress and minimum fatigue life at the corresponding position. The variation trend of stress and fatigue life at the corresponding position after fillet optimization was also discussed. The results showed that the equivalent stress of autoclave teeth without fillet optimization reached the maximum under different fillet sizes. The equivalent stress and fatigue life of the autoclave tooth were the same as the rounded corner size obtained by the optimization design. The optimal global solution could be obtained through the optimization design process.